(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
There is no doubt though all endemic industrial must be accompanied by environmental contamination problem that is closely linked increased industrial activity on the one hand and increase the size of the problem put this industrial waste on the other, and therefore the risk to natural resources and ecosystems as a result of the presence of development projects (especially industrial ones) so it was There must be a sound footing for the sitting of industrial zones and see how their commitment to the appropriate conditions to preserve the environment and enact strict laws to achieve this and prepared well prepared to avoid the numerous errors at the social, economic and technical, environmental and health.